2022-RA-1312-ESGO Feasibility of carboplatin monotherapy versus carboplatin-paclitaxel in frail elderly epithelial ovarian cancer patients. (20th October 2022) - Yu, Tamara; Kesmez, Ronas Taner; Flynn, MJ; Ledermann, JA; Lockley, M; MacDonald, N; McCormack, M; Nicum, S; Crusz, SM; Miller, RE; Merry, Eve
Abstract : Introduction/Background: Frail elderly patients with ovarian cancer (OC) are often treated with 3-weekly carboplatin (3wC) rather than carboplatin-paclitaxel (CP). Elderly Women with OC (EWOC)-1 trial demonstrated that 3-weekly carboplatin-paclitaxel (3wCP) achieved better survival outcomes and was more feasible (defined as the ability to complete 6 chemotherapy cycles without disease progression, death, or premature discontinuation due to toxicity) than 3wC in patients ≥ 70 years old (≥ 70 yo) with FIGO stage III/IV OC. We compared the feasibility of treatment with 3wC or 3wCP in frail elderly OC patients. Methodology: Data from two cancer centres was retrospectively analysed for newly-diagnosed stage III/IV OC patients ≥ 70 yo treated with 3wC or 3wCP. Frailty was scored using the Charlson-Comorbidity Index (CCI) and ECOG performance status. Toxicity was graded using CTCAE v5.0. Results: 107 patients received 3wC (n=31) or 3wCP (n=76, 2 receiving 3wC with weekly paclitaxel). Patients treated with 3wC rather than 3wCP were older ((median age 83 vs. 75 (p<0.001)) with more comorbidities ((median CCI 4 vs. 3 (p<0.001)). Treatment was discontinued for 4 of the 31 (13%) 3wC patients and 6 of the 76 (8%) patients who received 3wCP, with death and disease progression the most common reasons for discontinuation respectively, although the difference in discontinuation rate was not significant (p>0.05). Dose reductions occurred in 16% (5/31) of patients who received 3wC and 57% (43/76) of patients treated with 3wCP, most commonly due to haematological toxicity and peripheral neuropathy respectively. Conclusion: In spite of the limitations of our retrospective analysis, 3wCP appears as feasible as 3wC monotherapy for frail ≥ 70 yo FIGO stage III/IV OC patients, in keeping with the EWOC-1 data, and should be considered in this cohort given that it has been shown to achieve better survival outcomes. Toxicity profiles differ and dose reductions may be required in each treatment arm.